Burnout symptoms and recovery processes in eight elite soccer coaches over 10 years - Hassmén, P.; Kenttä, G.; Hjälm, S.; Lundkvist, E.; Gustafsson, H. (International Journal of Sports Science & Coaching, 2019)
Elite sport can be stressful, which increases the risk for burnout symptoms to develop. Especially when not balanced with sufficient recovery. To study the burnout-recovery process, eight elite soccer coaches were followed for 10 years. All eight were active elite coaches at the inception of this study and reported elevated emotional exhaustion scores on Maslach`s Burnout Inventory Educators Survey (MBI-ES). The coaches completed MBI-ES three additional times (year 3, 7, and 10), and they were also interviewed on the same occasions. At the 3-year follow-up, seven of the eight coaches reduced their exhaustion scores. The coach presenting with unchanged scores both at the 3- and 7-year follow-up was the only one still coaching at the elite level. All coaches revealed during the interviews that they struggled to manage their work-life balance well; some worked too many hours, some experienced difficulty in managing conflicting role-demands, and some wrestled with external pressures. Their approach to recovery was, however, similar. Apart from moving away from coaching at the elite level, they unanimously mentioned that they changed their approach to coaching to make recovery possible. They achieved the latter by, for example, increasing control and delegating responsibility. According to our longitudinal results, burnout frequently regarded as an end-state can decrease over time. Provided that decisive action is taken to change situational factors and personal demands. This frequently meant withdrawing from coaching, which in turn explains why coach retention remains a serious challenge for most organizations with teams/athletes competing at the elite level.